Strengthening the conservation and sustainable use of plant genetic resources for food and agriculture in Mongolia - Bayarsukh, Noov (Mongolian Journal of Agricultural Sciences, 2015)
No Abstract Available Journal of agricultural sciences №15 (02): 173-179, 2015